A retrospective study of Yiqibushenhuoxue decoction for the treatment of chronic obstructive pulmonary disease. Issue 31 (August 2018) - Li, Zhuying; Tian, Chunyan; Wang, Xuehui; Wang, Liqin
Abstract : Abstract: This retrospective study aimed to investigate the effect and safety of Yiqibushenhuoxue decoction (YQBSHXD) for the treatment of chronic obstructive pulmonary disease (COPD). This study involved 120 cases of patients with COPD. These cases were assigned to an intervention group and a control group equally, 60 subjects each group. Patients in both groups underwent Salmeterol. In addition, the cases in the intervention group also received YQBSHXD. All cases received a total of 12 weeks treatment. The primary outcome of lung function was measured by forced expiratory volume in 1 second (FEV1 ), and FEV1 /forced vital capacity (FVC). The secondary outcomes included severity of dyspnea on exertion, evaluated by 6-minute walk test (6MWT) with measurement of 6-minute walk distance (6MWD); and quality of life, assessed by the St. George's Respiratory Questionnaire (SGRQ). In addition, adverse events (AEs) were also recorded in this study. All outcome measurements were assessed before and after 12-week treatment. After 12-week treatment, cases in the intervention group underwent YQBSHXD did not show better outcome in lung function improvement, measured by the FEV1 ( P = . 11), and FEV1 /FVC ( P = . 15), compared with those in the control group. However, YQBSHXD may help to alleviate the severity of dyspnea on exertion, as measured by 6MWD ( P = . 03), and to improve the quality of life, as assessed by the SGRQ ( P <  .01). Additionally, no significant differences in AEs were detected between the 2 groups. The results of this study showed that YQBSHXD may help to manage COPD after 12-week treatment, although the lung function has not been improved.